ENERGY AND ITS TYPES. - Raxmatullayev Shamsiddin Hakimboy o‘g‘li , (TADQIQOTLAR.UZ, 2024)
Abstract: Energy is a tool that we need to carry out any work or task in our daily life. Energy is a physical quantity that is transferred from one type to another and does not disappear by itself, as a unit (joule).